Makna dan metafora dalam puisi modern: Analisis semantik puisi perahu kertas oleh Sapardi Djoko Damono - Bahari, Mochammad Galung Setya (Maliki Interdisciplinary Journal, 2024)
Poetry is a written art form that invites readers to reflect on the meaning behind the words. In the context of modern poetry, poets often use language in profound and creative ways, creating meaning that is evocative and compelling. This research article investigates the meaning and metaphor in the poem "Perahu Kertas" by Sapardi Djoko Damono. This poem draws attention for its ability to combine words with contrasting meanings to convey a deep emotional message. The results of this research help to understand how language, symbolism, and linguistic creativity work together in modern poetry to create a richer understanding of human emotional reality. The poem "Perahu Kertas" by Sapardi Djoko Damono is not only a beautiful literary work, but also a deep emotional journey, which enriches our understanding of the use of language in literary arts.